Polyglutamine (PolyQ) Diseases: Genetics to Treatments. Issue 4 (May 2014) - Fan, Hueng-Chuen; Ho, Li-Ing; Chi, Ching-Shiang; Chen, Shyi-Jou; Peng, Giia-Sheun; Chan, Tzu-Min; Lin, Shinn-Zong; Harn, Horng-Jyh
The polyglutamine (polyQ) diseases are a group of neurodegenerative disorders caused by expanded cytosine– adenine–guanine (CAG) repeats encoding a long polyQ tract in the respective proteins. To date, a total of nine polyQ disorders have been described: six spinocerebellar ataxias (SCA) types 1, 2, 6, 7, 17; Machado–Joseph disease (MJD/SCA3); Huntington's disease (HD); dentatorubral pallidoluysian atrophy (DRPLA); and spinal and bulbar muscular atrophy, X-linked 1 (SMAX1/SBMA). PolyQ diseases are characterized by the pathological expansion of CAG trinucleotide repeat in the translated region of unrelated genes. The translated polyQ is aggregated in the degenerated neurons leading to the dysfunction and degeneration of specific neuronal subpopulations. Although animal models of polyQ disease for understanding human pathology and accessing disease-modifying therapies in neurodegenerative diseases are available, there is neither a cure nor prevention for these diseases, and only symptomatic treatments for polyQ diseases currently exist. Long-term pharmacological treatment is so far disappointing, probably due to unwanted complications and decreasing drug efficacy. Cellular transplantation of stem cells may provide promising therapeutic avenues for restoration of the functions of degenerative and/or damaged neurons in polyQ diseases.